The Association of Bladder Wall Thickness with Severity of Symptoms in Patients with Overactive Bladder - Adrian, Ronny; Bernolian, Nuswil; Fauzi, Amir; Saleh, Irsan (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To investigate the association of bladder wall thickness (BWT) with severity of symptoms in overactive bladder patients in Obstetrics and Gynecology Department Dr. Mohammad Hoesin general hospital Palembang. Methods: An analytical observational study was conducted at Gynecology clinic Dr. Mohammad Hoesin General Hospital Palembang from November 2015 to August 2016. Data were analyzed with SPSS 16.0 for Windows. Bivariate analysis with the Chi square and association Rank-Spearman test was used to assess the association between BWT and visual analog scale (VAS). Results: Fourty subjects were included in the study. The mean BWT in the overactive bladder group was thicker compared to those without overactive bladder (5.8522  0.5783 vs 5.2176  0.67937). There was significant association between BWT and overactive bladder complaints. Abnormal group (5mm) had 12 times risk of overactive bladder compared to normal sample (5mm) (p = 0.029, RR = 12). Conclusion: Thus, the thickness of the urinary bladder wall measured with ultrasound examination (USG) can be used to assess the status and degree of urinary disorders in women with complaints of painful urinate and urinary disorders.  Keywords: bladder wall thickness, detrusor overactivity, overactive bladder, visual analog scale